2018
DOI: 10.1016/j.devcel.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia Control Stem Cell Behavior and Stimulate Germline Proliferation in Filarial Nematodes

Abstract: Although symbiotic interactions are ubiquitous in the living world, examples of developmental symbioses are still scarce. We show here the crucial role of Wolbachia in the oogenesis of filarial nematodes, a class of parasites of biomedical and veterinary relevance. We applied newly developed techniques to demonstrate the earliest requirements of Wolbachia in the parasite germline preceding the production of faulty embryos in Wolbachia-depleted nematodes. We show that Wolbachia stimulate germline proliferation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 62 publications
2
57
0
Order By: Relevance
“…This inviability is likely caused by the requirement for Wolbachia in proper polarization of the first zygotic cell division, as noted earlier (see section Zygotic mitosis ). A subsequent study ( Foray et al 2018 ) revealed that the Wolbachia symbiont and the Brugia female have coevolved to jointly support oocyte proliferation. The dynamics of this proliferation differ markedly from that of Caenorhabditis , in that it occurs predominantly in a zone proximal to the distal stem cell niche, with the most distal cells represent a quiescent population ( Foray et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inviability is likely caused by the requirement for Wolbachia in proper polarization of the first zygotic cell division, as noted earlier (see section Zygotic mitosis ). A subsequent study ( Foray et al 2018 ) revealed that the Wolbachia symbiont and the Brugia female have coevolved to jointly support oocyte proliferation. The dynamics of this proliferation differ markedly from that of Caenorhabditis , in that it occurs predominantly in a zone proximal to the distal stem cell niche, with the most distal cells represent a quiescent population ( Foray et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A subsequent study ( Foray et al 2018 ) revealed that the Wolbachia symbiont and the Brugia female have coevolved to jointly support oocyte proliferation. The dynamics of this proliferation differ markedly from that of Caenorhabditis , in that it occurs predominantly in a zone proximal to the distal stem cell niche, with the most distal cells represent a quiescent population ( Foray et al 2018 ). Loss of Wolbachia stimulates ectopic proliferation in the distal zone, with the effect of exhausting the quiescent pool.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterium synthesizes haem, riboflavin (vitamin B2), and flavin adenine dinucleotide, which the parasite host is unable to synthesize and that have been inferred to play an important role in filarial reproduction and development, as well as nucleotides, which are required during oogenesis and embryogenesis [18,38,39]. In addition, members of the genus Wolbachia participate in pathways aimed at preventing apoptosis of filarial reproductive, embryonic and somatic cells [17,40], likely by the direct targeting of the apoptotic signalling cascade [41][42][43]. (reviewed by [13]).…”
Section: Are Helminth Microbiomes Key To Parasite Fitness?mentioning
confidence: 99%
“…The distal-most gonadal sheath cell pair, Sh1, covers germ cells from the edges of the DTC to the bend of the gonad ( Figure 1 A–E) [ 10 ]. An arrangement with a somatic gonad sheath cell close to the DTC is also found in the female of the filarial parasitic nematode Brugia malayi [ 16 , 17 ], a distant relative of C. elegans . This discovery changes the previous model in which germ cells proximal to the DTC and distal to the transition zone were thought to be in a “bare region” where they contacted no somatic cells, only the gonadal basement membrane and occasional thin DTC and sheath projections [ 11 ].…”
Section: Resultsmentioning
confidence: 99%